Immunization crisis, vaccine hesitancy and strategies to improve immunization rates in Pakistan - Nasar, Sitara; Khaliq, Hafiz Muhammad Haseeb (International Journal of Pathology, 2026)
Immunization is now discussed as a significant barrier to Pakistani vaccine hesitancy. Studies indicate that wrong treatment, ignorance and distrust towards governmental health education are significant factors that lead to refusal or postponement of Vaccination (1). High-risk district surveys indicate that vaccine safety, fear of adverse effects and conspiracy claims de-vaccinate large proportions of children putting them at risk (2). Inequity and poor coverage also have a relationship with socioeconomic factors, including household income, mother education, and access to healthcare, which further supports the connection between poor coverage and inequity. These findings reiterate the notion that the lapses in immunization occur not only because of individuals but also due to the general sociocultural and structural reasons.